Increased activity of MdFRK2, a high-affinity fructokinase, leads to upregulation of sorbitol metabolism and downregulation of sucrose metabolism in apple leaves. Issue 1 (1st December 2018) - Yang, Jingjing; Zhu, Lingcheng; Cui, Weifang; Zhang, Chen; Li, Dongxia; Ma, Baiquan; Cheng, Lailiang; Ruan, Yong-Ling; Ma, Fengwang; Li, Mingjun
Abstract: To investigate the functions of fructokinase (FRK) in apple ( Malus domestica ) carbohydrate metabolism, we cloned the coding sequences of MdFRK1 and MdFRK2 from the 'Royal Gala' apple. The results showed that MdFRK2 expression was extremely high in shoot tips and young fruit. Analyses of heterologously expressed proteins revealed that MdFRK2 had a higher affinity for fructose than did MdFRK1, with Km values of 0.1 and 0.62 mM for MdFRK2 and MdFRK1, respectively. The two proteins, however, exhibited similar Vmax values when their activities were significantly inhibited by high concentrations of fructose. MdFRK2 ectopic expression was associated with a general decrease in fructose concentration in transgenic lines. In leaves, increased FRK activity similarly resulted in reduced concentrations of glucose and sucrose but no alterations in sorbitol concentration. When compared with those in the untransformed control, genes involved in sorbitol synthesis ( A6PR ) and the degradation pathway ( SDH1/2 ) were significantly upregulated in transgenic lines, whereas those involved in sucrose synthesis ( SPS1 ) and other degradation processes ( SUSY4, NINV1/2, and HxK2 ) were downregulated. The activity of enzymes participating in carbohydrate metabolism was proportional to the level of gene expression. However, the growth performance and photosynthetic efficiency did not differ between the transgenic and wild-type plants. These results provide new genetic evidence to support the view that FRK plays roles in regulating sugar and sorbitol metabolism in Rosaceae plants. Sugar metabolism: a master regulator: An international study led by Mingjun Li at Northwest A&F University in Shaanxi, China, reveals that an enzyme regulating the utilization of fructose in apple plants, fructokinase 2 (FRK2), has a key role in sugar metabolism. Overexpressing the gene encoding FRK2 in apple plants did not affect their growth or levels of sorbitol, the major product of photosynthesis in these plants, but it significantly lowered the levels of fructose, glucose and sucrose in mature leaves and increased the levels of starch. Accordingly, the activity of enzymes involved in sucrose and glucose metabolism was downregulated, whereas the activity of those involved in sorbitol metabolism was upregulated. Future analysis of the fruit and flowers will shed further light on the role of FRK in controlling sugar levels and the distribution of carbon in apple plants.